2020
DOI: 10.2174/1389201021666200320140908
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Alleviates Renal Fibroblast Activation through AMPK and ERK Signaling Pathways In Vitro

Abstract: Aims: The purpose of this study was to investigate the influences of apigenin on proliferation, differentiation and function of renal fibroblast after TGF-β1 stimulation and to uncover the underlying mechanisms. Background: Renal fibrosis is a common pathway leading to the progression of chronic kidney disease. Activated fibroblasts contribute remarkably to the development of renal fibrosis. Although apigenin has been demonstrated to play a protective role from fibrotic diseases, its pharmacological effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Apigenin has been stated to modulate the MAPK/ERK signaling. It has shown to suppress the proliferative ability of MAPK/ERK through modulation of the expression of AkT, ERK, DR4/DR5 and NF-kB [70,71]. Apigenin administration promoted TRAIL-mediated apoptosis in human lung cancer cells [35].…”
Section: Mapk Signaling Modulation By Apigeninmentioning
confidence: 99%
“…Apigenin has been stated to modulate the MAPK/ERK signaling. It has shown to suppress the proliferative ability of MAPK/ERK through modulation of the expression of AkT, ERK, DR4/DR5 and NF-kB [70,71]. Apigenin administration promoted TRAIL-mediated apoptosis in human lung cancer cells [35].…”
Section: Mapk Signaling Modulation By Apigeninmentioning
confidence: 99%
“…Previous studies have shown the renoprotective effect of apigenin through the attenuation of renal fibrosis via activation of AMPK leading to the inactivation of the TGF-β1/Smad2/3 signaling pathway [ 182 , 183 ]. Uremia associated with the build-up of toxic compounds secondary to renal dysfunction is a major contributor to endothelial dysfunction and cardiovascular disease.…”
Section: Role Of Antioxidants In the Prevention Of Ckdmentioning
confidence: 99%
“…Through network pharmacology and liquid‐phase mass spectrometry techniques, API has been identified as one of the pharmacological substances that might contribute to the anti‐asthma effect of Loki Zupa decoction (Mohammadtursun et al, 2020; Wei et al, 2016; Wuniqiemu et al, 2021). API, previously reported to have good antioxidant and anti‐inflammatory activities, is a potent inhibitor of MAP kinase (Li et al, 2020; Salehi et al, 2019). Considerable literature demonstrates that API acts on the three major mitogen‐activated protein kinase (ERK, JNK, and p38) pathways, the NF‐κB pathway and the PI3K/Akt pathway, among other different anti‐inflammatory pathways, and can prevent IκB degradation, p65 subunit phosphorylation and nuclear translocation of NF‐κB, activate B cells, and inhibit COX‐2 activity (He et al, 2021; Li et al, 2020) In addition, API has been shown to enhance the expression of the cellular antioxidants SOD, CAT, and GSH‐Px, inhibit ROS and MDA production, and suppress lipid metabolism and oxidative stress abnormalities through Nrf2 and PPARγ (Feng et al, 2017; Wu et al, 2021; Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%